Field Training Monitoring of Alpine Ski Athletes Using a Triaxial Accelerometers - Jin Su Suk; SeoungKi Kang; Jae Hyung Lee; Young Ha Ji (Korea Institute of Sport Science, 2021)
PURPOSE This study was designed to propose a quantitative base training evaluation method through alpine ski training monitoring using a triaxial accelerometer. METHODS Twelve Korean alpine ski athletes, six each in France and New Zealand, participated in this study. Activity data during training and daily living were collected for 7 days via the Actigraph GT9X. The collected data were downloaded through ActiLife Ver 6.13.1. Energy expenditure was calculated with Freedson (2011), and the resting metabolic rate was corrected using the Harris & Benedict (1918) formula. Further, the physical activity intensity classification criteria and METs formula of Freedson (1998) were used to classify hourly activity intensity. The collected data were organized by date, time, intensity, and energy expenditure using Microsoft Excel 2016. Differences between weekdays vs. weekends and skiing vs. physical training were analyzed through a paired sample t-test using Windows SPSS 23 with a significance level of a=.05. RESULTS First, both groups showed repetitive on and off high-intensity activities during scheduled ski training and competition. Second, moderate-intensity activities accounted for an average of 6-10%, and the weekly total time and intensity of MVPA was very high. Finally, the group from France showed differences in total energy expenditure during weekdays vs. weekends (p<.05) and the energy expenditure of both ski training and physical training during weekdays vs. weekends (p<.05). The New Zealand group showed a difference in total energy consumption during weekdays vs. weekends (p<.05). CONCLUSIONS A systematic training program based on quantitative training evaluation should be developed for alpine ski athletes to maintain proper rest and exercise intensity levels.